2006
DOI: 10.1115/1.2717616
|View full text |Cite
|
Sign up to set email alerts
|

Control of Vortex Shedding From a Bluff Body Using Imposed Magnetic Field

Abstract: The two-dimensional incompressible laminar viscous flow of a conducting fluid past a square cylinder placed centrally in a channel subjected to an imposed transverse magnetic field has been simulated to study the effect of a magnetic field on vortex shedding from a bluff body at different Reynolds numbers varying from 50 to 250. The present staggered grid finite difference simulation shows that for a steady flow the separated zone behind the cylinder is reduced as the magnetic field strength is increased. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The variation is nearly linear within the selected ranges of the parameters. In this respect the flow behaviour is identical to the flow about a square cylinder (Singha et al , 2007). The variations in Strouhal number with Hartmann number for different Reynolds numbers are shown in Figure 9(b).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The variation is nearly linear within the selected ranges of the parameters. In this respect the flow behaviour is identical to the flow about a square cylinder (Singha et al , 2007). The variations in Strouhal number with Hartmann number for different Reynolds numbers are shown in Figure 9(b).…”
Section: Resultsmentioning
confidence: 90%
“…It is seen that the unsteady flow at higher Reynolds numbers need stronger magnetic field to become steady. It is also observed that the threshold or critical Hartmann number for suppressing the shedding of vortices completely is marginally higher for the circular cylinder compared to a square cylinder (Singha et al , 2007). The difference is negligible at the Reynolds number of 150, but increases slowly with increasing Reynolds number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of vortex shedding from a bluff body using imposed magnetic field was studied numerically by Singha et al (2007). A 2-D incompressible laminar viscous flow past a square obstacle placed inside the channel was considered.…”
Section: Control Of Vortex Shedding By Electrical Methods (Ehd)mentioning
confidence: 99%
“…In addition to the above-mentioned methods, some researchers have introduced the effects of magnetic field on hydrodynamics and heat transfer. Singha et al [29] numerically studied the confined flow over a square cylinder in the presence of a transverse magnetic field. Their results show that the variation of Reynolds number and Hartmann number has the same trend for elimination of the vortex shedding.…”
Section: Introductionmentioning
confidence: 99%